Effects of Diclofenac Sodium on Renal Parenchyma and Prevention by Vitamin-E in Adult Albino Rats (Medical Forum Monthly, 2024)
ABSTRACTObjective: To determine the preventive role of Vitamin E on renal parenchyma after given of Diclofenac Sodium in albino rats.Study Design: Experimental StudyPlace and Duration of Study: This study was conducted in the Department of Anatomy Baqai Medical University and Muhammad Medical College, Mirpurkhas from June 2011 to November 2011,Materials and Methods: For this experimental study , 30 albino rats were taken. They were divided into three groups ; A, B and C. The animals in group-A given normal saline 10 ml/kg per day. Group-B received diclofenac sodium 2 mg/kg per day and group-C receives diclofenac sodium 2mg/kg/day dissolved in distilled water with vitamin-E 2 mg/kg/day dissolved in olive oil administered half an hour before the diclofenac sodium by feeding tube per day for 2 weeks. On day 15 all animals were sacrificed with deep ether anesthesia. Their kidneys were removed, fixed in 10 % formalin. Representative blocks were taken and embedded in liquid paraffin. For routine histological examination 5 µm thick section cut by microtome and stained with H&E, PAS and silver methenamine. Renal histology was done under light microscope to see the proximal and distal tubular diameter and count.Result: No significant (P>0.05) changes were observed in the histopathology of kidney tissues of the groups A and C rats. The group B significantly (P<0.001) affected the histopathology of kidney.Conclusion: It may be concluded that diclofenac sodium produces changes in kidney, which may be attributed to ischaemia induced by inhibition of prostaglandin synthesis resulting in tubular necrosis in albino rats simultaneous administration of vitamin-E partially protect the morphological and histological changes induced by diclofenac sodium.